(untitled) (Zoo Botanica, 2025)
Visceral leishmaniasis (VL) or Kalazar, is a vector-borne parasitic disease caused by Leishmania donovani, which is spread through the bite of sand flies from infected animals or humans. The disease continues to be a major health concern due to limited treatment options. One of the key proteins involved in the viability of the parasite is N-myristoyltransferase (NMT), making it a prominent target for new drug development. Development of new drugs require a lot of resources and time. The current study was designed to find potential L. donovani NMT inhibitors from the existing drugs used for other disease through insilico studies. To identify potential inhibitors for NMT, the 3D structure of the L. donovani NMT was obtained from the protein data bank. More than one hundred and fifty potential FDA approved drugs were retrieved from chemspider. These drugs were docked using the online PatchDock server, selecting the top results. The interactions were visualized using GS Viewer and LIGPLOT. The interactions formed include hydrogen bonding, covalent interactions, and hydrophobic interactions with the key active site residues of the target, suggesting at potential mechanism of inhibition. The present study successfully identified promising potential inhibitors of L. donovani NMT. The drugs that showed maximum interactions includes Clarithromycin, Amoxicillin, Bacampicillin and Ciprofloxacin which could serve as candidates for experimental testing in future studies. The findings of the current study lay the foundation for developing new treatments for visceral leishmaniasis.